Tổng hợp điện hóa màng natri hydroxyapatit trên nền thép không gỉ 316L - Hạnh, Võ Thị; Năm, Phạm Thị; Thơm, Nguyễn Thị; Hải, Đỗ Thị; Mai Thanh, Đinh Thị (Vietnam Journal of Chemistry, 2017)
Sodium dope hydroxylapatite (NaHAp) were deposited on the 316L stainless steel (316L SS) substrates by electrodeposition technique. The influences of precursor solution concentration, scanning potential ranges, scaning times, scanning rates and temperature to deposit NaHAp coating were researched. The analytical results of FTIR, SEM, Xray, AAS, thickness and adhension of the obtained coating at the solution containing Ca(NO3)2 3×10-2 M, NH4H2PO4 1.8×10-2 M and NaNO3 0.06 M; scanning potential ranges of 0÷-1.7 V/SCE; scaning times of 5; scanning rates of 5 mV/s showed that NaHAp coating was sigle phase, plate shape, dense and uniform with average size about 150×25 nm, thickness 7.8 µm, adhesion strength 7.16 MPa and Na+ ions doped on HAp with mass percentage of 1.5 %. Keywords. 316L SS, electrochemical deposition, sodium dope hydroxyapatite coating.